Experiences of follow-up after treatment in patients with prostate cancer: a qualitative study. - O'Brien, R; Rose, P; Campbell, C; Weller, D; Neal, R; Wilkinson, C; Watson, E (2010)
OBJECTIVE: To develop an understanding of experiences of follow-up in patients with prostate cancer, to seek explanations as to why men's needs might not be well met, and explore views on the possible role of primary care in follow-up. The experiences of these patients, and views on the delivery of follow-up care, have been relatively neglected compared to those diagnosed with other cancers. PATIENTS AND METHODS: In all, 35 patients were recruited from 20 practices across three regions in the UK. Maximum variation was sought by purposely sampling by age (59-82 years), treatment, length (0.75-14 years) and mode of follow-up. RESULTS: Patients' descriptions of the content and organization of follow-up showed the shortcomings of follow-up, which included system failings causing patients to be lost to follow-up, and unmet psychosexual needs. Patients were mainly positive about the prospect of follow-up taking place outside the hospital setting. However, some expressed concerns about current follow-up practices and suggested several improvements that need considering if primary care were to take a greater role. CONCLUSION: This study identified some general deficiencies with the current system of follow-up, and our data indicate that primary care could have a role in addressing some of these.